The Evolution of Communication Pedagogy - Jerry D. Feezel (Central States Communication Association, 2018)
This article is an overview of the major developments in the field of communication in education. From the history of the national association over 100 plus years, specific attention is paid to changes leading to the advent of this publication. Changes in nomenclature, conferences, publications, research, and educational trends are discussed. The essay is intended to provide a view of history as setting for inauguration of the Journal of Communication Pedagogy. It also is intended to invite and stimulate other scholars' reflections on the nature and evolution of the field.